2000
DOI: 10.1016/s0749-3797(99)00118-x
|View full text |Cite
|
Sign up to set email alerts
|

Reviews of evidence regarding interventions to improve vaccination coverage in children, adolescents, and adults11The names and affiliations of the Task Force members are listed on page v of this supplement and at http://www.thecommunityguide.org22Some of this material was published previously in: Shefer A, Briss P, Rodewald L, et al. Improving immunization coverage rates: an evidence-based review of the literature. Epidemiol Rev 1999;20:96–142.

Abstract: Background: This paper presents the results of systematic reviews of the effectiveness, applicability, other effects, economic impact, and barriers to use of selected population-based interventions intended to improve vaccination coverage. The related systematic reviews are linked by a common conceptual approach. These reviews form the basis for recommendations by the Task Force on Community Preventive Services (the Task Force) regarding the use of these selected interventions. The Task Force recommendations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
106
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 469 publications
(109 citation statements)
references
References 158 publications
(293 reference statements)
3
106
0
Order By: Relevance
“…Briss et al 16 identify incentives as interventions that increase demand for vaccinations. These are likely to include both rewards for immunising and penalties for not immunising.…”
Section: Current Guidance On Increasing Vaccination Coverage and Decrmentioning
confidence: 99%
See 1 more Smart Citation
“…Briss et al 16 identify incentives as interventions that increase demand for vaccinations. These are likely to include both rewards for immunising and penalties for not immunising.…”
Section: Current Guidance On Increasing Vaccination Coverage and Decrmentioning
confidence: 99%
“…As such, and following Briss et al, 16 we restrict our definition of incentives to interventions that increase demand for vaccinations by offering contingent rewards with real material value (whether or not these are offered in the form of cash), but widen this to include interventions imposing contingent penalties with real material value (again, whether or not these are imposed in the form of cash).…”
Section: Current Guidance On Increasing Vaccination Coverage and Decrmentioning
confidence: 99%
“…9 This leaves many unprotected when the virus begins circulating. 12 Although reminder-recall systems that notify families that their child needs a vaccine are widely recommended, 13,14 traditional strategies implemented via mail or telephone have had limited to no efficacy in urban, low-income, and minority populations [15][16][17] who are also at high risk for undervaccination. 18,19 We recently demonstrated the effectiveness of using text message reminders for first influenza vaccine doses in this population.…”
Section: What This Study Addsmentioning
confidence: 99%
“…2 Multicomponent interventions aimed at increasing immunization coverage rates are more successful than single interventions, perhaps with the exception of patient reminder and recall systems. [3][4][5] The most successful interventions described allow families to explain their health concerns, address perceived barriers to vaccination, improve community awareness of services already available, and engage health care outreach liaisons as a bridge to medical providers. 3,6 Similarly, studies have shown the importance in identifying communitywide partners for collaborative efforts in improving a program' s impact.…”
mentioning
confidence: 99%
“…[3][4][5] The most successful interventions described allow families to explain their health concerns, address perceived barriers to vaccination, improve community awareness of services already available, and engage health care outreach liaisons as a bridge to medical providers. 3,6 Similarly, studies have shown the importance in identifying communitywide partners for collaborative efforts in improving a program' s impact. 7,8 We collaborated with our local health department and our largest communitybased organization (CBO), the Salvation Army, to reach resource-poor families and their children, address individual vaccine concerns, and educate regarding vaccine importance and safety in an effort to increase immunization coverage rates in this high-risk population.…”
mentioning
confidence: 99%